Statistical analysis of factors influencing health literacy level using multiple linear regression analysis / Norshaieda Abdullah ...[et al.] - Abdullah, Norshaieda; Azizan, Nurul Hafizah; Mahzan, Siti Mahirah; Ismail, Nik Amirul Shakir; Iskandar Hassan Tan, Nurul Khaimnnisa Tan (Universiti Teknologi MARA, Kelantan, 2023)
Health literacy is defined as the ability to receive, read, comprehend, and use healthcare information to make informed health decisions and follow treatment guidelines. It is one of the most critical aspects of health promotion. Limited health literacy is also accounted for adverse health outcomes and a huge financial burden on society. The aim of this cross-sectional study is to identify on how gender, income, and attitude towards a healthy lifestyle can influence health literacy level. The objectives of this study are to determine the relationship between gender, financial status, and attitude towards a healthy lifestyle towards health literacy level and to determine the most influential factors between gender, income and attitude towards a healthy lifestyle that affect health literacy level. 301 samples out of 1369 undergraduate students in UiTM Cawangan Kelantan, Kampus Kota Bharu (UiTM KB) has been chosen by using stratified random sampling. This study is a consequence of a lack of study about the health knowledge level among university students. The instrument used to evaluate the students' health literacy was the European Health Literacy Survey Questionnaire (HLSEU-16). The methods used were correlation analysis and multiple regression analysis. The findings show that the level of health literacy among university students is sufficient at the rate of 37 out of 50 points. Furthermore, health literacy among students explained by their attitude towards healthy lifestyle was 84.9%, whereas gender and income level were not significant factors determining health literacy level.